(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The study aimed to demonstrate the effect of effective opportunistic thinking (flexible thinking, divergent thinking, constructive thinking and categorical beliefs) on strategic decisions of University of Wasit. To reach this goal, we relied on the descriptive analytical approach to describe the variables of the study (effective open thinking, strategic decisions). In addition, to analyzing the data collected from (45) individuals who represented the study sample, namely the senior management of University of Wasit (the university president and his assistants, the college dean and his assistants). The questionnaire used as the main tool for collecting data and then analyzing it using the statistical program (SPSSV.23) in order to reach the results of the study. The study conclusions of the study was that results of the statistical analysis showed that the senior management of Wasit University has the ability to manage and think positively and openly in order to reach an effective strategic decision. One of the most important recommendations that came out of the study was enhance aspects of intellectual and effective openness on a sustainable basis in order to reach strategic decisions capable of developing University of Wasit.